Efficient Labor and Capital Income Taxation over the Life Cycle - Sebastian Findeisen; Dominik Sachs (University of Mannheim, Department of Economics, 2014)
This paper analyzes Pareto optimal taxation of labor and capital income in a lifecycle framework with private information and idiosyncratic risk. We focus on historyindependent tax systems. We thereby complement the Mirrlees taxation literature, which has so far typically either characterized optimal history-dependent distortions or focused on static environments. For labor income taxes, we provide a novel decomposition of tax formulas into a redistribution and an insurance component. The latter is independent of redistributive motives and is determined by the degree of income risk and risk aversion. We show that the optimal linear capital tax rate is non-zero and derive a simple formula, which trades off redistributive and insurance benefits against the efficiency loss from savings distortions. Our quantitative results show that the insurance component contributes significantly to optimal labor tax rates. Optimal capital taxes are significant and yield sizable welfare gains.
urn:nbn:de:bsz:180-madoc-366276
Keywords: H21; H23; 330; Optimal Dynamic Taxation; Capital Taxation; First-Order Approach